When Things Go Awry: Command Responsibility, Death Marches, and Unforeseeable Circumstances - Guiora, Amos N.; Jackson, Nathan H. (American Journal of Trade and Policy, 2021)
Although the events of the past year are in many ways unprecedented, they have resulted in circumstances that are common throughout history. The rise of a global pandemic has led to suffering in many forms, political powers shifting, militant coups rising, and countries facing protests as civil unrest becomes more prevalent. In these uncertain times, political leaders and the role of militaries have been even more scrutinized, revealing flaws that might have remained undetected if it was not for circumstances going awry. These current events have caused us to reflect upon incidents of the past when commanders have faced the uncertainty of how to complete their mission. History is wrought with instances in which the commander, despite having a “Plan B,” still fails to succeed in his role, thus resulting in hundreds of thousands of unnecessary lives lost. Specifically, this article focuses on three death marches—The Long Walk of the Navajo, The Bataan Death March, and Holocaust Death Marches—and the international law of command responsibility. In comparing and contrasting these three historic events through the lens of this law, we analyze the imposition of a commander’s criminal liability when unexpected events occur and he or she is called upon to make difficult decisions. In doing so, we also provide a historical backdrop of each commander’s ethical, moral, and tactical decisions, allowing us to explore what else could have been done, and who should be held liable for the actions of the commander’s soldiers. Ultimately, we call on national leaders and military commanders alike to evaluate our uncomfortable contemporary reality, look back in history, and ask themselves one question: am I truly prepared to make the right decisions when things go wrong?